The Development of Hopping: An observation Checklist for Educators: 單足跳的進展程度: 教育者的觀察清單 - NONIS, Karen P.; PARKER, Helen E.; LARKIN, Dawne (Asian Journal of Physical Education & Recreation, 2004)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. This paper provides an observation checklist of the developmental stages of components of repetitive hopping-in-place and describes performance differences in hopping on the preferred and the non-preferred foot by children and adults. Females aged 3-7 years and 18-30 years performed the task of hopping-in-place on their preferred and non-preferred limb on three separate sessions. A behavioural checklist was used to describe the developmental sequence for leg and arm actions, trunk lean, balance control and foot landing style. Age differences in developmental levels in component actions were revealed in both the preferred and non-preferred limbs. The utility of a checklist which details the developmental stages of component parts of hopping and the need to analyse preferred and non-preferred limbs to more objectively quantify the quality of performance are discussed. 這份報吿提供「重複單足跳」發展階段的觀察清單，並形容對於成人和小孩在選擇「較喜歡」與「較不喜歡」的腳之間單足跳的不同表現。女性年齡介於三至七歲和十八至三十歲參與了這項選擇「較喜歡」與「較不喜歡」的腳之間單足跳的三個各別測試。對於腿和臂的行動、腿部肌肉(trunk lean)、身體平衡的控制和足的著陸風格則是以一份行為式的清單來形容。年齡的差距在發展水準的組成部分上對於選擇「較喜歡」與「較不喜歡」的腳之間單足跳有一定的影響力。使用檢查單可更客觀地詳述對以上單足跳的發展階段以及分析在選擇「較喜歡」與「較不喜歡」的腳之間的需要。